2005
DOI: 10.1021/jp051031p
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray Studies of Al1-yTiy Formation and Re-hydriding Inhibition in Ti-Enhanced NaAlH4

Abstract: NaAlH4 samples with Ti additives (TiCl3, TiF3, and Ti(OBu)4) have been investigated by synchrotron X-ray diffraction in order to unveil the nature of Ti. No crystalline Ti-containing phases were observed after ball milling of NaAlH4 with the additives, neither as a solid solution in NaAlH4 nor as secondary phases. However, after cycling, a high-angle shoulder of Al is observed in the same position with 10% TiCl3 as that with 2% Ti(OBu)4, but with considerably higher intensity, indicating that the shoulder is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 30 publications
10
109
1
1
Order By: Relevance
“…This accords with previous reports that the NaAlH 4 obtained from the hydrogenation of stoichiometric amounts NaH and Al* contains significant amounts of residual Al and Na 3 AlH 6 owing to the formation of an Al 0.85 Ti 0.15 solid solution. 15,16 Accurate quantification of the Al species present in the reaction mixtures is not feasible as Al in the probe contributes (albeit minimally) to the intensity of the Al metal resonance. Moreover, the resonance for alumina contained in the tube (3) overlaps with the alanate peaks.…”
Section: Q4mentioning
confidence: 99%
“…This accords with previous reports that the NaAlH 4 obtained from the hydrogenation of stoichiometric amounts NaH and Al* contains significant amounts of residual Al and Na 3 AlH 6 owing to the formation of an Al 0.85 Ti 0.15 solid solution. 15,16 Accurate quantification of the Al species present in the reaction mixtures is not feasible as Al in the probe contributes (albeit minimally) to the intensity of the Al metal resonance. Moreover, the resonance for alumina contained in the tube (3) overlaps with the alanate peaks.…”
Section: Q4mentioning
confidence: 99%
“…Although many models were proposed to describe (de)hydrogenation of Ti-doped NaAlH4, no clear consensus about structures and catalytic mechanism of Ti in NaAlH4 has been achieved. The only established fact from these studies is a surface-localized species containing a nascent binary phase Ti-Al alloy formed during cyclic dehydriding and rehydriding processes [28,43,51,[56][57][58].…”
Section: Doping Transition Metalmentioning
confidence: 99%
“…More importantly, thermodynamics of hydrogen desorption/adsorption of complex metal hydrides usually can be adjusted by controlling particle size [34,[99][100][101][102][103]. Particle size of complex metal hydrides can be usually reduced to ~200 nm by ball milling technique, for NaAlH4 preferably in the presence of TMbased catalysts [57,104,105]. Obtaining smaller certain sizes of particles of complex metal hydrides is still challenging.…”
Section: Nanoengineering Techniquesmentioning
confidence: 99%
“…Experimental EXAFS studies by Chaudhuri et al [16] also showed the formation of stable intermetallic species resembling TiAl 3 . Brinks et al [17,18] have showed the formation of a solid Al 12x Ti x solution with x , 0.07 after cycling at 1608C. Haiduc et al [19] found an hcp-Ti(Al) solid solution after doping with TiCl 3 , and an XRD-amorphous phase when NaAlH 4 was doped with Ti(OBu) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, extensive experimental [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and theoretical 6,21-29 studies are done that shed light on various phenomena, including formation of solid Ti-Al, TiAl 3 alloy, as well as Ti-Al-H compounds, along with Al clustering; however, a clear understanding of the thermodynamic profiles of hydrogen desorption in Ti-doped sodium alanates is still lacking.…”
Section: Introductionmentioning
confidence: 99%